Sustainability humanistic education within an Asian context - Raphaely, T.; Marinova, Dora (World Scientific, 2018)
Humanistic. Education. within. an. Asian. Context. Talia Raphaely and Dora Marinova 1. Introduction Educating people about sustainability is a complex task. Yet, as the planet moves from the life-supporting Holocene into the Anthropocene  ...